Low tuberculosis case detection: A community and health facility based study of contributory factors in the Nkwanta South district of Ghana - Amenuvegbe, G.K.; Francis, A.; Fred, B. (BioMed Central Ltd., 2016)
Background: Tuberculosis (TB) continues to pose a major public health problem globally. In Ghana, the national TB case detection rate is 81 %; however, some districts are not able to meet their case detection targets. This study was therefore carried out in the Nkwanta South district to identify possible factors contributing to low TB case detection. Methods: A cross sectional descriptive study involving the review of outpatients records for the year 2012 was conducted. Data on cough for 2 weeks or more duration, age, sex, area of residence and sputum smear examination were extracted. A community-based survey involving household contacts of TB patients and community based volunteers was also carried out. Data collected in the community included knowledge of TB status of relatives, level of socialization with TB patients and signs and symptoms of TB disease. Descriptive statistics including cross-tabulations were used to identify possible factors contributing to low TB case detection. Results: A total of 932 patients out of 3987 reported coughing for 2 weeks or more (23.4 %; 932/3987). Out of that, only 24.6 % (230/932) had sputum smear microscopy done, yielding 57 (24.8 %) positive cases. Five out of the 57 positive cases were found not registered for the initiation of treatment leading to a false primary default rate of 8.8 % per year. Eighty-five percent of the contacts were able to mention persistent cough as a sign/symptom of TB with 80.4 % indicating that TB can be cured. Only 10 % of health facilities provided diagnostic services in the district with only 25 % of staff having had training in TB management. Conclusion: The study identified some factors (weak record review systems, inadequate diagnostic centres, lack of trained persons and some level of stigma at the community level) that could be contributing to low TB case detection in the Nkwanta South district.
Keywords: Case detection; Community-based volunteers; Nkwanta